Awareness of Custom Officers on Counterfeit Pharmaceutical Products And The Roles Of Pharmacy Enforcement Officers - Chuo, Yew Ting; Hiram, Ting; Yee, Chang Soh; Abu Hassan, AAJ; Kah, Seng Lee (Phcog.Net, 2017)
Background: Counterfeit pharmaceutical products (CPP) is a lucrative business for illegal operators who constantly try to smuggle their products into Malaysia. Full understanding of the roles and duties of pharmacy enforcement division as well as CPP by Royal Malaysian Custom (RMC) officers are pre-emptive to optimize the operation against drug smuggling.